Impact of Physical Activity Programs on Job-Related Stress among Healthcare Personnel (The International Journal for Scientific Research, 2023)
Introduction: Stress is a prevalent issue among healthcare workers, impacting their mental health, job satisfaction, and the quality of care provided to patients. Physical activity is recognized as a potential intervention for reducing stress, but its effectiveness specifically within healthcare settings remains underexplored. This systematic review aimed to evaluate the impact of physical activity programs on job-related stress among healthcare workers, synthesizing the latest evidence to guide clinical practice and policy. Methods: A comprehensive search of electronic databases, including PsycINFO, Scopus, and Web of Science, was conducted for studies published up to 2022. The review focused on interventional studies and clinical trials that assessed the effectiveness of physical activity interventions in reducing occupational stress among healthcare workers. Only articles published in English were considered. Inclusion criteria targeted randomized controlled trials, quasi-experimental studies, and controlled before-and after studies that reported quantitative outcomes on stress levels. The methodological quality of included studies was assessed, and data extraction focused on intervention details, sample sizes, and stress outcome measures. Results: Twelve studies were included, with sample sizes ranging from 20 to 200 participants. Interventions varied from structured exercise programs and aerobic exercises to yoga and mindfulness-based physical activities. The review found significant reductions in occupational stress, with risk ratios of interventions indicating a 10% to 30% decrease in stress levels. Aerobic and mindfulness-based activities were particularly effective, demonstrating a notable impact on reducing stress among healthcare workers. Conclusions: The systematic review provides strong evidence that physical activity interventions can significantly reduce occupational stress among healthcare workers. Given the variability in intervention effectiveness, healthcare institutions should consider implementing tailored physical activity programs as part of their employee wellness strategies.
Keywords: Stress; Physical Activity; Healthcare Workers; Interventional Studies